Educating and engaging a new target audience about the problem of pain for society. Issue 6 (December 2022) - Devonshire, Elizabeth; Dodds, Stella; Costa, Daniel; Denham, Rebecca; Fitzgerald, Kylie; Schneider, Carl R
Background: Pain education initiatives are typically targeted at health professionals, with less attention being placed on the education of other target audiences. Recent curriculum changes across undergraduate liberal studies degree programs at The University of Sydney presented an opportunity to develop an online course entitled Health Challenges: Pain and Society, which was aimed at a non-traditional target audience. To promote student engagement about the problem of pain for society, the course was designed using the Community of Inquiry framework.Research Design: This paper reports on an Educational Design Research study, investigating the effectiveness of the course in engaging students across two cohorts, in 2019 and 2020.Data Collection: Learning analytics were collected from the Learning Management System each year. The level of student engagement in non-assessable tasks was measured using multiple linear regression. Students' degree type and majors were recorded. In 2020, the quality of student workbook responses was recorded.Results: In both cohorts, engagement with the workbooks was a predictor of academic achievement. In 2020, a significant interaction effect between quantity and quality of engagement was observed.Conclusions: Our findings highlight the importance of designing online learning to facilitate successful engagement for non-traditional target audiences about the issue of chronic pain for society.